Early Maternal Spatial Support for Toddlers and Math Skills in Second Grade. Issue 2 (14th March 2020) - Ribeiro, Luisa A.; Casey, Beth; Dearing, Eric; Nordahl, Kristin Berg; Aguiar, Cecília; Zachrisson, Henrik
ABSTRACT: The aim of this study is to investigate whether maternal spatial support during two types of joint manipulative toy play tasks with 2-year-old children was longitudinally associated with math screening test scores in second grade. The interaction between spatial support and maternal education was explored as well. We also investigated predictions of a teacher rating of math performance at second grade, although these effects were less robust. Data were drawn from BONDS (The Behavior Outlook Norwegian Developmental Study), a longitudinal study of Norwegian children and their families. Participants were a subsample of 932 mothers and their 2-year-olds. Mothers were asked to help their children solve both a puzzle task and a shape-color sorting task. Mothers' spatial support included spatial language, gestures, and placement of objects. Results showed that higher levels of spatial support during mother-child interaction tasks at 2 years of age was significantly associated with fewer math difficulties in second grade. This was the case for a puzzle task (a task associated with spatial visualization skills), but not for a shape-color sorting task (a task associated with shape and color feature discriminations). Conclusions are drawn with respect to the importance of identifying optimal parental spatial strategies associated with better math outcomes. These findings on parental facilitation of spatial skills during joint early play may be useful for future training interventions directed at parents of children at risk for poor math skills.